IMPLEMENTASI ALGORITMA NAIVE BAYES DALAMMENENTUKAN KARYAWAN TETAP PADA PERUSAHAANWILLSON SURYA UNGGUL TANGERANG - Muhamad Willy Setiawan (2021)
The company PT. Willson Surya Unggul is one of the companies engaged in the business of making electrical cables and the like. This study aims to predict the level of accuracy in the appointment of contract employees that can support the company in making decisions, especially regarding promotions to permanent employees at PT. Willson Surya Unggul. This is motivated by the difficulty of determining whether or not an employee who has been promoted to a promotion has been promoted, because the system is not yet computerized and employee data documents are piled up. In this study, the data used is data on contract employees at PT. Willson Surya Unggul Tangerang and the method used is the Naïve Bayes Classifier algorithm method. And to find out how well the Naïve Bayes Classifier algorithm is used in this study, the RapidMiner software is used to perform the test. From the test in RapidMiner, the accuracy value is 69.70% and the ROC value is 0.748, which means that the Naïve Bayes Classifier algorithm is very well used in this study. After testing using RapidMiner software and getting the test results. The prediction results obtained are in accordance with the calculation results obtained from the RapidMiner software and manual calculations. Based on the research that has been done that results in a level of accuracy and prediction that can analyze the decisions of employees being appointed so that they can be applied to PT. Willson Surya Unggul Tangerang so as to make it easier to determine the feasibility of promotions for employees.